Pediatrics hearing loss journey: from universal newborn hearing screening through cochlear implantation: From newborn hearing screening through cochlear implantation - Kaewsiri Isaradisaikul, Suwicha; Plodpai , Yuvatiya; Tanamai, Napas; Pitathawatchai, Pittayapon; Kiatthanabumrung, Sivaporn (Thai Journal of Otolaryngology Head and Neck Surgery, 2025)
Hearing impairment can be screened from birth. If diagnosed, treated, and received hearing rehabilitation, the patient should have better language and speech development, enable verbal communication, access to education in regular schools, and have a good quality of life. Currently, Thailand has made progress in providing diagnostic and treatment services for hearing loss. Hearing-loss children can access hearing rehabilitation with hearing aids and cochlear implants. However, the shortage of audiology professionals may limit access to these services. This article compiles guidelines for newborn hearing screening, diagnosis and rehabilitation of hearing loss in children, hearing rehabilitation devices, and the issuance of disability certificates for hearing impairment, to serve as a guide for health personnel involved in this field.